Penerapan Framework Laravel dalam Pengembangan Aplikasi Manajemen Keuangan Santri Berbasis Barcode di Pondok Pesantren Sabilul Hasan - Arifin, Zainal; Faid, Mochammad (Universitas Nurul Jadid, 2024)
The management of student payments in Islamic boarding schools (pondok pesantren) often faces various challenges, particularly in terms of manual record-keeping, delayed reporting, and limited access to information for parents or guardians. Pondok Pesantren Sabilul Hasan Genggong in Probolinggo Regency is one such Islamic educational institution that requires a more efficient and transparent payment system. The purpose of this study at Pondok Pesantren Sabilul Hasan Genggong is to develop a student financial management application with a barcode feature using the Laravel framework, aimed at providing convenience for parents in monitoring the status of educational payments easily and in real-time. The system development in this research adopts the Waterfall model, a sequential approach consisting of several stages: Requirements Analysis, System Design, Implementation, verification, and Maintenance. In the implementation process, the Laravel framework is integrated with MySQL as the data storage medium. This research results in an information system capable of managing financial operations, particularly payment processes, generating accurate financial reports, and providing payment information access to parents through barcode scanning. With the implementation of this system, payment management in the pesantren becomes more structured, minimizes record-keeping errors, and enhances transparency and ease of access for parents. This system is expected to serve as an effective solution in supporting the digital transformation of financial administration within the pesantren environment.